1977
DOI: 10.1180/minmag.1977.041.320.04
|View full text |Cite
|
Sign up to set email alerts
|

The nature of kerolite, its relation to talc and stevensite

Abstract: SUMMARY. Kerolites from Goles Mountain (Yugoslavia), Wiry (Poland), Madison Co. (North Carolina), and Kremze (Czechoslovakia) are compared with talc and stevensite. Chemical analyses give a composition for kerolite near R3Si4010(OH)2.nH20 with R mainly Mg and n about 0.8-I.2. Infra-red data and dehydration-rehydration experiments suggest that the additional water is partly surface-held hydrogen-bonded molecular water, lost up to about 3oo ~ and easily recoverable, and 'water' held as surface hydroxyls, lost at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
97
1
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 8 publications
13
97
1
1
Order By: Relevance
“…The kerolite used in this study was from Carter's Mine, Madison County, North Carolina, and was described by Brindley et al (1977). Individual crystallites are plates about 150/~ in diameter in plan.…”
Section: Starting Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…The kerolite used in this study was from Carter's Mine, Madison County, North Carolina, and was described by Brindley et al (1977). Individual crystallites are plates about 150/~ in diameter in plan.…”
Section: Starting Materialsmentioning
confidence: 99%
“…They argued that the presence of H20 in the interlayer was not responsible for the increase in the basal spacing. Brindley et al (1977) found that weight loss due to dehydration was gradual between 110 ~ and 700~ The dehydration was completely reversible after heating to 300~ and 70-90% reversible after heating to 650~ On the basis of the gradual weight loss, its variable rehydration potential, and infrared (IR) data showing several frequencies attributed to molecular water and hydroxyl groups, they speculated that water in kerolite could reside in a number of locations, such as layer surfaces and edges. They suggested that most of the water was present as Copyright 9 1991, The Clay Minerals Society adsorbed molecular water and as surface hydroxyls, with a small amount possibly retained in the hexagonal tings of the tetrahedral sheet.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations